Baseline Knowledge of Potential Pet Toxins among the US General Public. Issue 3 (3rd July 2019) - Young, Natalie; Royal, Kenneth; Lovee, Bryan; Davidson, Gigi
ABSTRACT: In 2014, the American Society for the Prevention of Cruelty toAnimals Animal Poison Control Center fielded more than 167, 000cases of potential nonhuman animal toxicosis. Concomitantly, thereremain limited free and reputable veterinary toxicology resourcesavailable for companion-animal (pet) caregivers (owners) seekingassistance and advice about potentially harmful exposures inanimals. The objective of this study was to assess pet toxicantknowledge among a representative sample of Americans andgauge the need for additional toxicology resources. The studyinvolved a survey designed to capture participants' ability to identifypotential animal toxicants and what resource they would use ifan accidental toxic ingestion occurred. Participants were ableto correctly identify 52% of potential pet toxins. Women, olderparticipants and participants from the South expressed moreconcern about each potential pet poison. Approximately halfof participants indicated they would consult a veterinarian andwhereas most others indicated they would search the Internet formore information about pet toxicology. The findings suggest moreveterinary poisoning education is needed for pet owners to be ableto accurately distinguish potential pet toxicants from nontoxicants.